Analysis of DC MCB Usage Characteristics for AC and DC Load Usage - Sarwan Hamid; Jamaaluddin Jamaaluddin; Dwi Hadidjaja Rasjid Saputra; Arief Wisaksono (Universitas Muhammadiyah Sidoarjo, 2022)
One of the most important and expensive power lines in the distribution method is the low line voltage. In case of overload or short circuit current, it protects the electrical installation. MCB is an important component in electrical installations. The formation of sparks due to a short circuit can eventually cause a fire which has the potential to cause a fire, which is an unwanted MCB nuisance. This MCB can be used as a direct current breaker with a load, either manually or automatically. When the MCB is switched from